(3GdYdGFb GdeZQHjI GdLRGFQjIs
(3ChdgG (B:s
(3heeG jfNQW ai Sdc gPG eG Sdcg ai ENeGO GdaJfI ef hdGjI GdJQc HhWf GdLRGFQ hQYjJge s
(3BNQgG (B:s
(3hNQL Cgd aGS CjVkG Yf WGYJg hJQZjHge ai eMHJg hfUQJg hGdCeQ ddg gh GdMGce dGeYbH dMceg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B151 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B_ (3GdQHGW (B(1492(3O(B) s
Keywords: (3GdJGQjNs